Credit markets and bubbles: is the benign credit cycle over? - Altman, Edward I.; Kuehne, Brenda J. (Economics and Business Review, 2016)
Bubble theories are becoming quite common these days for several asset classes, and in important growth areas of the world, like China, India and the U.S. Are we in the midst of an inflating credit bubble and, if so, when is it likely that the bubble will burst? Contrarily, are we experiencing an extended period of opportunistic debt financing? The evidence we have compiled leads us to conclude that, indeed, a bubble is building, but it is not likely to explode dramatically, with a significant increase in corporate bond and loan defaults, until at least late 2016 or more likely in 2017–2018. We believe that if not for the enormous credit stimuli by all of the major Central Banks of the world, the most recent benign credit cycle, one of over six years now, would be over, and a new stressed cycle would be starting. That is, the match (cycle) is now in “extra-time.”